Efeito da quercetina na pancreatite aguda induzida por ceruleína em camundongos - Carvalho, Karine Maria Martins Bezerra (2010)
Quercetin is a plant-derived flavonoid widely known by its anti-oxidant and antiinflammatory properties. Acute pancreatitis (AP) is a disease with a high morbidity and mortality and a complex pathophysiology, with variable involvement of regional tissues or organ systems. Despite of extensive investigations into this disease entity, to date there exists no specific medical treatment for AP. In this study, quercetin was investigated for its effect on the severity of cerulein-induced acute pancreatitis in mice. Male Swiss mice were treated with quercetin (25, 50 and 100 mg/kg, p.o.), vehicle (2% DMSO in distilled water, 10 ml/kg) or thalidomide (200 mg/kg, p.o.), 1 h before administration of cerulein (5 x 50 μg/kg, 1 h apart). A group treated with saline (0.9% NaCl) was also included. The effects of treatments on pancreatic edema, serum amylase and lipase enzymes and cytokines (TNF- , IL-6, IL-1 and IL-10), myeloperoxidase activity (pancreas and lung), pancreatic thiobarbituric acid reactive substances (TBARS), non-protein-sulfidryl groups (NP-SH), histopathology of pancreas and lung and immunostaining for TNF- expression in pancreas were analysed. Cerulein significantly increased pancreatic edema and serum levels of amylase, lipase, TNF- , IL-6 and IL-1 and decreased IL-10 levels. Histopathologic evaluation revealed the presence of edema, neutrophil infiltration, hemorrhage, acinar vacuolization and necrosis of the pancreas and lung hemorrhage. Besides, we observed a marked increase in the expression of TNF- in immunohistochemical analysis. The pre-treatment with quercetin (25, 50 and 100 mg/kg, p.o.) or thalidomide (200 mg/kg, p.o.) significantly attenuated the severity of acute pancreatitis induced by cerulein, as evidenced by significant reductions in pancreatic serum enzymes lipase and amylase and the pancreatic inflammation, evidenced by suppression of neutrophil infiltration, TNF-a, IL-1b and IL-6 cytokine production and the TNF-a expression. Further, it enhanced the IL-10 cytokine production and demonstrated an antioxidant action through a decrease in the levels of TBARS and restoration of pancreatic NP-SH. Quercetin could also attenuate the systemic repercussion in the lung evidenced by suppression of neutrophil infiltration (MPO) and decrease of lung hemorrhage (histology). In conclusion, this study provides the first evidence to show that quercetin attenuates the development of cerulein-induced acute pancreatitis through the anti-inflammatory and antioxidant mechanisms.